Flow‐Induced Long‐Term Stable Slippery Surfaces. Issue 11 (7th April 2019) - Baumli, Philipp; Teisala, Hannu; Bauer, Hoimar; Garcia‐Gonzalez, Diana; Damle, Viraj; Geyer, Florian; D'Acunzi, Maria; Kaltbeitzel, Anke; Butt, Hans‐Jürgen; Vollmer, Doris
Abstract: Slippery lubricant‐infused surfaces allow easy removal of liquid droplets on surfaces. They consist of textured or porous substrates infiltrated with a chemically compatible lubricant. Capillary forces help to keep the lubricant in place. Slippery surfaces hold promising prospects in applications including drag reduction in pipes or food packages, anticorrosion, anti‐biofouling, or anti‐icing. However, a critical drawback is that shear forces induced by flow lead to depletion of the lubricant. In this work, a way to overcome the shear‐induced lubricant depletion by replenishing the lubricant from the flow of emulsions is presented. The addition of small amounts of positively charged surfactant reduces the charge repulsion between the negatively charged oil droplets contained in the emulsion. Attachment and coalescence of oil droplets from the oil‐in‐water emulsion at the substrate surface fills the structure with the lubricant. Flow‐induced lubrication of textured surfaces can be generalized to a broad range of lubricant–solid combinations using minimal amounts of oil. Abstract : The shear‐induced lubricant‐depletion of slippery surfaces is overcome by replenishment via flowing emulsions for different combinations of lubricants and hydrophobic porous substrates. Above a threshold velocity, starting with an initially water‐filled substrate, lubricant droplet attachment to features of the substrate takes place, and the surface gets filled with lubricant. The addition of surfactant overcomes electrostatic repulsion between lubricant droplets.